BEBAN KERJA DAN MOTIVASI DENGAN KINERJA TENAGA KESEHATAN SAAT COVID 19 - Indah, Fenita Purnama Sari; Listiana, Ida; Nilawati, Nadia (Edu Masda Journal, 2022)
The workload during the Corona Virus Disease 2019 (Covid-19) pandemic has increased and this condition causes fatigue and stress. In Indonesia, the results of the study show that around 66% of respondents from 644 health workers experience anxiety, 55% stress and 23.5% depression due to (Covid-19). The purpose of this study was determine the relationship between workload and motivation with the performance of health workers at the Tangerang City Health Office in 2021. This study is a quantitative study with a research design used is a cross-sectional approach with a total sample of 78 health workers at the Tangerang City Health Office. From the results of the study showed that the performance of health workers was good, which was as many as 67 respondents (85.9%), while the performance of health workers was not good as many as 11 respondents (14.1%), the workload was not good as many as 65 respondents (83.3%). The motivation is not good 20 respondents (25.6%). The results of statistical tests then there is a relationship between workload (workload) and health worker performance (value p = 0.002) and there is a relationship between motivation and health worker performance (value p = 0.002). It is expected that the Tangerang City Health Office will increase the number of health workers, especially during the Covid-19 pandemic, this is intended so that there is no high workload for every health worker and is advised to increase motivation by providing recognition and appreciation, so that health workers are motivated to further improve their performance.